2008
DOI: 10.1007/s10592-008-9517-1
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite and mtDNA analysis of the population structure of grey seals (Halichoerus grypus) from three breeding areas in the Baltic Sea

Abstract: The growing number of grey seals in the Baltic Sea has led to a dramatic increase in interactions between seals and fisheries. The conflict has become such a problem that hunting was introduced in Finland in 1998 and the Swedish Environment Protection Agency recommended a cull of grey seals starting in 2001. Culling has been implemented despite the lack of data on population structure. Low levels of migration between regions would mean that intensive culling in specific geographic areas would have disproportio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 31 publications
4
32
1
Order By: Relevance
“…Differentiation between South Australian and Western Australian colonies is not surprising considering the distance (>2200 km) between these two regions. However in comparison to other pinniped studies conducted at similar or larger spatial scales the F ST values reported here between these two regions were higher (Hoelzel et al, 2001;Palo et al, 2001;Coltman et al, 2007;Graves et al, 2009;Andersen et al, 2011;Feijoo et al, 2011). Strong genetic partitioning between South Australian and West Australian colonies is also evident with mtDNA data (significant pairwise ST values ranged from 0.83 to 0.94, Campbell et al, 2008).…”
Section: Genetic Diversity and Differentiationcontrasting
confidence: 57%
See 1 more Smart Citation
“…Differentiation between South Australian and Western Australian colonies is not surprising considering the distance (>2200 km) between these two regions. However in comparison to other pinniped studies conducted at similar or larger spatial scales the F ST values reported here between these two regions were higher (Hoelzel et al, 2001;Palo et al, 2001;Coltman et al, 2007;Graves et al, 2009;Andersen et al, 2011;Feijoo et al, 2011). Strong genetic partitioning between South Australian and West Australian colonies is also evident with mtDNA data (significant pairwise ST values ranged from 0.83 to 0.94, Campbell et al, 2008).…”
Section: Genetic Diversity and Differentiationcontrasting
confidence: 57%
“…However, significant structuring was also detected between colonies separated by only 120-160 km, well within realistic swimming distances for Australian sea lions. The level of genetic differentiation at these relatively short spatial scales is above that detected in other pinnipeds (e.g., gray seal (Halichoerus grypus) Allen et al, 1995;Graves et al, 2009, Harbor seal (Phoca vitulina) Goodman, 1998 Lancaster et al, 2010). This high level of genetic differentiation has implications in terms of vulnerability to any threatening processes and in particular, local fisheries interactions (Goldsworthy et al, 2009) are likely to have strong regional effects.…”
Section: Genetic Diversity and Differentiationmentioning
confidence: 89%
“…The reassessment was based on three different datasets: i) the 40 grey seal haplotypes posted in GenBank (accession numbers AM287215-AM287254) by Graves et al [8]; ii) the raw ABI chromatograms from Graves et al [8], covering three different grey seal breeding sites in the Baltic Sea: the Bay of Bothnia (BB), Estonia (EST), and the Stockholm Archipelago (STA); and iii) an “erroneous” dataset constructed from the GenBank haplotypes and the information on haplotype distribution in Table 5 of the Graves et al study [8]. Specifically, we first downloaded the haplotypes listed in GenBank and assembled them with zero mismatches in order to assess the actual number and types of haplotypes in the data listed in GenBank.…”
Section: Methodsmentioning
confidence: 99%
“…In our ongoing study of grey seal population dynamics we were interested in using the information of Graves et al [8] and the corresponding mtDNA haplotype data in GenBank to recreate their mtDNA dataset. A closer examination of the GenBank data revealed that several of the haplotypes in the GenBank repository were identical.…”
Section: Introductionmentioning
confidence: 99%
“…For grey seal, we selected the data of Graves et al (2009) re-edited by Fietz et al (2013). In addition, new data were generated using the primer pair ThrL16272 and DLH16750 (Stanley et al 1996) on DNA extracts of 8 grey seals (GenBank accession numbers KM053398−KM053405) and 97 faecal samples of grey seals from various locations in the Dutch North Sea and Wadden Sea (GenBank accession numbers KM066992-KM067088).…”
Section: Primer Designmentioning
confidence: 99%